Internal photoemission spectroscopy : principles and applications - Afanasev, V. V. (Elsevier, 2008)
The monographic book addresses the basics of the charge carrier photoemission from one solid to another - the internal photoemission, (IPE) - and different spectroscopic applications of this phenomenon to solid state heterojunctions. This is the first book in the field of IPE, which complements the conventional external photoemission spectroscopy by analysing interfaces separated from the sample surface by a layer of a different solid or liquid. IPE is providing the most straightforward and, therefore, reliable information regarding the energy spectrum of electron states at interfaces. At the same time, the method provides the unique capability of analysing the heterostructures relevant to the modern micro- and nano-electronic devices as well as new materials involved in their design and fabrication. In addition to the discussion of fundamental physical and technical aspects of IPE spectroscopic applications, several hot topics are addressed. These include development of new insulating materials for advances Si MOS technology (both high-k gate insulators and low-k dielectrics for interconnect insulation), metal gate materials, development of heterostructures based on high-mobility semiconductors, etc. Thanks to a considerable activity in this field over the last few years, the recent results concerning band structure of most important interfaces involving novel materials can now be documented. - First complete description of the internal photoemission phenomena - A practical guide to internal photoemission measurements - Describes reliable energy barrier determination procedures - Surveys trap spectroscopy methods applicable to thin insulating layers - Provides an overview of the most recent results on band structure of high-permittivity insulating materials and their interfaces - Contains a complete collection of reference data on interface band alignment for wide-bandgap insulating materials in contact with metals and semiconductors.